Reversible cerebral vasoconstriction syndrome–related headache and delayed cerebral infarction: a mini review - Zhang, Xinxin; He, Xu; Zhang, Jieying; Zhu, Qian; Jin, Pukai; Yang, Jin (Frontiers in Neuroscience, 2025)
Reversible cerebral vasoconstriction syndrome is a major cause of thunderclap headache and a preventable source of delayed ischaemic stroke. Despite expanding recognition, diagnosis is often delayed because early neuroimaging may be normal and vasoconstriction peaks in weeks two to three, and management remains experience-based rather than trial-anchored. In this mini-review we summarize advances in clinicoradiological definition and pathophysiology of tone dysregulation, outline risk-stratified diagnostic pathways built on serial CTA/MRA with confirmatory DSA when needed, high-resolution vessel-wall MRI to exclude inflammatory arteriopathy, perfusion MRI/CT and arterial spin labeling, and bedside transcranial Doppler, and appraise translational opportunities spanning time-anchored surveillance, perfusion-preserving care bundles and pragmatic endpoints. We also discuss enduring challenges—including nosological overlap with primary CNS vasculitis, non-standardized imaging schedules, heterogeneous blood-pressure targets and a paucity of randomized data—that temper implementation. By integrating time-aware vascular and perfusion readouts (e.g., planned week-2–3 repeat angiography, ASL hypoperfusion mapping, sustained Doppler velocities) with trigger withdrawal, cautious blood-pressure management and symptomatic vasodilators such as calcium-channel blockers and magnesium in selected contexts, emerging strategies aim to preserve cerebral perfusion, anticipate delayed infarction and standardize follow-up across settings. Our synthesis provides an appraisal of the evolving landscape of RCVS care and outlines pragmatic standards and avenues for prospective evaluation. We hope these insights will assist researchers and clinicians as they endeavor to implement more effective, individualized regimens.